Molecular identification, probiotic characterization, anticancer assessment, and encapsulation of lactic and acetic acid bacteria isolated from Iranian traditional dairy products - Haghshenas, Babak (2015)
Lactic and acetic acid bacteria (LAB and AAB) are generally recognized as safe microorganisms. Their increasing demand in food industry has motivate this present study to perform molecular identification, in vitro characterization, anticancer assessment and microencapsulation of probiotics from traditional dairy products produced in the west of Iran region. Cancer epidemiology showed lower cases recorded in this region compared with other areas in Iran which can be associated with the daily dietary intake of people living in these areas. Dairy products made from the west of Iran employs traditional methods involving no antibiotics in the animal feed and often contained higher acidity compared with commercial dairy products. Probiotic bioactive compounds have fewer side effects with low-cost when use in chemotherapy. Thus, the identification of probiotic bacteria exhibiting anticancer property isolated from dairy products for medicinal purposes is highly desirable. The isolated bacteria from 5 types of traditional dairy products were identified and clustered into 5 genera (Lactococcus, Leuconostoc, Lactobacillus, Enterococcus, and Acetobacter) with 12 species, 4 subspecies, and 27 strains using combination of different molecular techniques (namely 16S rRNA sequencing, (GTG)5-PCR, and ARDRA).In vitro characterization showed 11 isolates displaying high anti-pathogenic activity and antibiotic susceptibility. Their survival rates in the harsh gastrointestinal conditions were also high, calculated at >70%. Cytotoxic assays indicated that extracted metabolites from Acetobactersyzygii38Lac, Enterococcus durans 39C, and Lactococcus lactis subsp. lactis 44Lac displayed high anticancer activity against AGS, MCF-7, HT29, and HeLa cancer cell lines but not on normal cell lines. Pronase assay revealed that proteins contained in the metabolites play a key role in anticancer properties of these isolates. Incidence of apoptosis was detected in the isolates on the basis of the morphological assessments via fluorescent microscope and flow cytometry. To improve delivery and prolong the survival rate of probiotic in the gastrointestinal tract, encapsulation approach was investigated using a simple extrusion method. Nine formulations using different blend of alginate with pysllium or fenugreek were designed and investigated aiming at improving the encapsulation efficiency. Results showed 2% (w/v) alginate, 1.5% (w/v) alginate +0.5% (w/v) psyllium, and 1.5% (w/v) alginate + 0.5% (w/v) fenugreek formulations, with >98% encapsulation efficiency, high stability during 28 days of storage and displayed high survival rates in harsh gastrointestinal conditions (>80 %), which were significantly (P < 0.01) higher than the non-encapsulated bacteria (>62%). Incorporation of 0.5% (w/v) fenugreek and psyllium into 1.5% (w/v) alginate gel resulted in enhanced encapsulation properties. For psyllium-alginate formulation, additional properties such as high growthstimulating effects of probiotic and smaller bead sizes were observed. Acetobacter strains were isolated for the first time from traditional dairy products, which is a new finding of this study. Their extracted metabolites displayed high cytotoxicity effects on various cancer cell lines comparable to commercial cancer drug, Taxol. Development of a new encapsulated probiotic formulation using fenugreekalginate blend was also a success. The formulation showed significant improvement in the delivery of probiotic in gastrointestinal system. In conclusion, probiotic bacteria were successfully isolated and characterized from Iranian traditional dairy products. These probiotics exhibited antimicrobial activity, antibiotic resistance and anticancer activity thus these make bacteria potential candidates for the development of nutraceutical products. In addition, the study demonstrates the improved survival and delivery of probiotics in the gastrointestinal conditions system by using encapsulation technique.